An analytical approach for on‐site analysis of breath samples for Δ9‐tetrahydrocannabinol (THC) - Henion, Jack; Hao, Changtong; Eikel, Daniel; Beck, Olof; Stambeck, Peter (JOURNAL OF MASS SPECTROMETRY, 2024)
Increased acceptance of cannabis containing the psychoactive component, Δ9‐tetrahydrocannabinol (THC), raises concerns about the potential for impaired drivers and increased highway accidents. In contrast to the “breathalyzer” test, which is generally accepted for determining the alcohol level in a driver, there is no currently accepted roadside test for THC in a motorist. There is a need for an easily collectible biological sample from a potentially impaired driver coupled with an accurate on‐site test to measure the presence and quantity of THC in a driver. A novel breath collection device is described, which includes three separate sample collectors for collecting identical A, B, and C breath samples from a subject. A simple one‐step ethanol extraction of the “A” breath collector sample can be analyzed by UHPLC/selected ion monitoring (SIM) liquid chromatography/mass spectrometry (LC/MS) to provide qualitative and quantitative determination of THC in breath sample in less than 4 min for samples collected up to 6 h after smoking a cannabis cigarette. SIM LC/MS bioanalyses employed d3‐THC as the stable isotope internal standard fortified in negative control breath samples for quantitation including replicates of six calibrator standards and three quality control (QC) samples. Subsequent confirmation of the same breath sample in the B collectors was then confirmed by a reference lab by LC/MS/MS analysis. Fit‐for‐purpose bioanalytical validation consistent with pharmaceutical regulated bioanalyses produced pharmacokinetic (PK) curves for the two volunteer cannabis smokers. These results produced PK curves, which showed a rapid increase of THC in the breath of the subjects in the first hour followed by reduced THC levels in the later time points. A simpler single‐point calibration curve procedure with calibrators and QC prepared in ethanol provided similar results. Limitations to this approach include the higher cost and operator skill sets for the instrumentation employed and the inability to actually determine driver impairment.